The death and dying process: definitions of nursing undergraduate students - Sales, Catarina Aparecida; Ferreira, Patrícia Chatalov; Silva, Vladimir Araujo da; Oliveira, William Tiago de; Marcon, Sonia Silva (Rev Rene, 2013)
The purpose of the study was to know the definitions nursing students have concerning the death-dying process. A descriptive-qualitative study developed in 2010, with 65 students of the first and last year of Nursing in a public university. Data was collected through semi-structured interview and submitted to content analysis. Data showed that the students possess diverse opinions concerning this process, per times seeing it as natural however difficult to be understood and accepted, especially because it brings pain, suffering, losses and family unstableness. They also revealed that they do not feel prepared to experience terminality in their future customers. The results reinforce the importance of having the thematic approached in the beginning of the undergraduate course, in curricular components or in extra-curricular activities, in order to provide the development of necessary support to experiencethe death-dying process of the customers.DOI: https://doi.org/10.15253/2175-6783.2013000300008